2019
DOI: 10.30599/jti.v11i1.385
|View full text |Cite
|
Sign up to set email alerts
|

Eksperimen Mandiri Siswa dalam Penentuan Percepatan Gravitasi Bumi pada Materi Gerak Jatuh Bebas

Abstract: Siswa selalu berpikir bahwa jumlah massa mempengaruhi percepatan jatuh benda vertikal. Melalui eksperimen mandiri yang dilakukan siswa kelas X, akan mengubah cara berpikir siswa dengan benar. Tujuan penelitian ini adalah menentukan berapa waktu tempuh yang dimiliki dua benda yang mengalami gerak jatuh bebas dengan massa yang berbeda. Eksperimen menggunakan media gerak jatuh bebas yang terintegrasi oleh komputer/laptop. Eksperimen didampingi oleh guru, kemudian mereka menyimpulkan sendiri hasil dari analisis ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…In learning physics, students are invited to think about finding solutions to problems associated with the theory (Fatimah et al, 2020). Physics learning should provide direct experience to students to increase the ability to construct, understand, and apply the concepts that have been learned (Firdaus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In learning physics, students are invited to think about finding solutions to problems associated with the theory (Fatimah et al, 2020). Physics learning should provide direct experience to students to increase the ability to construct, understand, and apply the concepts that have been learned (Firdaus et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Keadaan bumi yang manusia tempati tidaklah bulat sempurna, jari-jari bumi di khatulistiwa 21 Km lebih besar dari pada jari-jari bumi di kutub (Lasiman, 2007). Semakin tinggi suatu tempat dari permukaan laut maka, semakin kecil percepatan gravitasinya (Firdaus et al, 2019). Dari beberapa penelitian yang sudah dilakukan perlu dilakukan verifikasi dalam variasi yang berbeda dan sangat penting untuk dijadikan bahan ekperimen sebagai informasi pengetahuan bagi pebelajar, dalam penelitian ini menyoroti variasi nilai percepatan gravitasi terhadapa ketinggian MDPL permukaan Bumi, karena beberapa teori menyatakan bahwa percepatan gravitasi dipengaruhi oleh posisi ketinggian dan massa benda sehingga besar percepatan gravitasi di Bumi tiap tempat itu akan berbeda.…”
Section: Pendahuluanunclassified
“…The range, breadth and depth of topics discussed at each level vary according to the area of expertise of the lecturer/teacher [3]. Even though the concept of free fall motion has been obtained before and is often found in everyday life, there are still many students who experience misconceptions about speed, free fall acceleration and gravitational acceleration [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Free fall motion media is used in physics learning to visually explain to students the concept of free fall motion. This media is proven to reduce misconceptions and increase understanding of physics concepts [4]. It was also revealed that most students had misconceptions about acceleration, assuming that in each case it would have the same impact, namely acceleration depending on the motion of the object [3].…”
Section: Introductionmentioning
confidence: 99%